Platelets in Skin Autoimmune Diseases - Liu, Xiaobo; Gorzelanny, Christian; Schneider, Stefan W. (Frontiers in Immunology, 2019)
Systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and small vessel vasculitis are three autoimmune diseases frequently manifested in the skin. They share common pathogenic features, including production of autoantibodies, loss of tolerance to self-antigens, tissue necrosis and fibrosis, vasculopathy and activation of the coagulation system. Platelets occupy a central part within the coagulation cascade and are well recognized for their hemostatic role. However, recent cumulative evidence implicates their additional and multifaceted immunoregulatory functions. Platelets express immune receptors and they store growth factors, cytokines and chemokines in their granules enabling a significant contribution to inflammation. A plethora of activating triggers such as damage associated molecular patterns (DAMPs) released from damaged endothelial cells, immune complexes, or complement effector molecules can mediate platelet activation. Activated platelets further foster an inflammatory environment and the crosstalk with the endothelium and leukocytes by the release of immunoactive molecules and microparticles. Further insight into the pathogenic implications of platelet activation will pave the way for new therapeutic strategy targeting autoimmune diseases. In this review, we discuss the inflammatory functions of platelets and their mechanistic contribution to the pathophysiology of SLE, SSc, ANCA associated small vessel vasculitis and other autoimmune diseases affecting the skin.